Production of a Naphthoquinone Pigment by a Species of Streptoverticillium and Its Accumulation by a Streptomycete - Tresner, H. D. (1971)
A naphthoquinone pigment produced by a species of Streptoverticillium was accumulated by a Streptomyces sp. when the two organisms were grown in mixed cultures.